Antibody constant region peptides can display immunomodulatory activity through activation of the Dectin-1 signalling pathway. - Elena Gabrielli; Eva Pericolini; Elio Cenci; Claudia Monari; Walter Magliani; Tecla Ciociola; Stefania Conti; Rita Gatti; Francesco Bistoni; Luciano Polonelli; Anna Vecchiarelli (PLoS ONE, 2012)
We previously reported that a synthetic peptide with sequence identical to a CDR of a mouse monoclonal antibody specific for difucosyl human blood group A exerted an immunomodulatory activity on murine macrophages. It was therapeutic against systemic candidiasis without possessing direct candidacidal properties. Here we demonstrate that a selected peptide, N10K, putatively deriving from the enzymatic cleavage of the constant region (Fc) of human IgG(1), is able to induce IL-6 secretion and pIkB-α activation. More importantly, it causes an up-regulation of Dectin-1 expression. This leads to an increased activation of β-glucan-induced pSyk, CARD9 and pIkB-α, and an increase in the production of pro-inflammatory cytokines such as IL-6, IL-12, IL-1β and TNF-α. The increased activation of this pathway coincides with an augmented phagocytosis of non opsonized Candida albicans cells by monocytes. The findings suggest that some Fc-peptides, potentially deriving from the proteolysis of immunoglobulins, may cause an unexpected immunoregulation in a way reminiscent of innate immunity molecules.